2000
DOI: 10.1002/(sici)1097-4644(20000201)76:2<244::aid-jcb8>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of glutamate dehydrogenase as another isoprotein binding to the membrane of rough endoplasmic reticulum

Abstract: Glutamate dehydrogenase (GDH) was purified from rough endoplasmic reticulum (RER) in rat liver using anion‐exchange and affinity chromatography. As GDH has been known as an enzyme that exists mainly in the matrix of mitochondria, the properties of purified GDH were compared with those of mitochondrial GDH. The GDH activity in 0.1% Triton X‐100‐treated RER subcellular fraction was nearly the same as intact RER, whereas that of the mitochondrial fraction increased by 50% after the detergent treatment. In kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…These observations agree with those derived from tissue fractionation studies (Colon et al 1986;Lee et al 1999) and ER-immunogold labeling (Aoki et al 1987) showing that GDH localizes predominantly to mitochondria and to a lesser extent so to the ER. On the other hand, Rosso et al (2008) have suggested that the signal sequence of hGDH2 shows enhanced mitochondrial targeting properties as compared to hGDH1.…”
Section: Subcellular Destination Of Human Gdhssupporting
confidence: 90%
See 1 more Smart Citation
“…These observations agree with those derived from tissue fractionation studies (Colon et al 1986;Lee et al 1999) and ER-immunogold labeling (Aoki et al 1987) showing that GDH localizes predominantly to mitochondria and to a lesser extent so to the ER. On the other hand, Rosso et al (2008) have suggested that the signal sequence of hGDH2 shows enhanced mitochondrial targeting properties as compared to hGDH1.…”
Section: Subcellular Destination Of Human Gdhssupporting
confidence: 90%
“…This particulate-bound GDH resisted extraction by TritonX-100 and sonication, although it could be largely extracted (about 60%) by the cationic detergent CTAB and to a lesser extent (about 25%) by 0.5 M NaCl or 0.5 M KCl. Similarly, Lee et al (1999) obtained GDH from a rat liver ER fraction (105,0009g for 60 min) that was not extractable by TritonX-100, although it was partially extractable (40%) by 0.6 M NaCl. Others have reported that GDH is also located in the cell nucleus (di Prisco and Casola 1975).…”
Section: Subcellular Destination Of Human Gdhsmentioning
confidence: 99%
“…A recent study of chicken liver GDH [31] confirmed the nuclear localization of this enzyme [26,27,28,29] by uncovering the ability of GDH to act as a serine protease of histone H3 [31]. GDH was also found in the granular endoplasmic reticulum of rat liver [32]. Another form of GDH, which was localized in lysosomes and endosomes, has a tubulin-binding activity in the presence of ATP in vitro [33].…”
Section: Intracellular Localization Of Gdh In Animalsmentioning
confidence: 94%
“…The existence of membrane-bound GDH forms has been shown by various researchers [24,25,27,32]. For example, a membrane-bound isoform resistant to extraction by detergents such as digitonin, deoxycholate and Triton X-100, but solubilized with cationic detergents (hexadecyltrimethylammonium bromide), and to a lesser extent with 0.5 M NaCl or KCl, is present in rat brain [27].…”
Section: Intracellular Localization Of Gdh In Animalsmentioning
confidence: 99%
“…Indeed, in yeast, aconitase deficiency causes glutamate auxotrophy because of the lack of ␣-ketoglutarate generation (53). GDH, an enzyme with numerous isoforms in mammalian tissues (56), is found in mitochondrial and other cellular compartments, including cytosolic extracts of retina (2,10,37,57,59). GDH is present in both the retina and the retinal pigment epithelium (42).…”
mentioning
confidence: 99%